Incidence of fluorosis in patients in a university hospital setting. - S, SHEBI; SUGUMARAN, DR.SURENDAR; DR.SURESH, (The journal of contemporary issues in business and government, 2021)
Dental fluorosis is recognized as an oral health disease of public health importance by the WHO.Dental fluorosis results in poor esthetic appearance which may have a psychological bearing and lead to low confidence. In today’s competitive world, these factors have gained much importance.To assess the incidence of fluorosis patients in young adults underwent routine dental check up with regards to age and gender. This is a descriptive clinical study carried out in saveetha Dental college and hospitals, Poonamallee chennai which was conducted using the patient record from the Department of Endodontics. Sample data has been collected from reviewing the case record of patients who visited clinics for dental checkup. All the patients who suspected fluorosis and who came for routine dental check up were selected for assessment of DF, Deans fluorosis index is used. Total of 283 patients,69.1% were male and 30.9% were female.Mean age between 20-30 years of age group and the mild fluorosis is higher in percentage about 46.5%. In moderate fluorosis, P value is 0.03 which was statistically significant compared to other types of fluorosis and the male predilection is more compared to females. Within limits of the study,mild fluorosis is present more compared to Dean’s fluorosis index and male preditection is more. It is necessary to conduct a community based programme to determine other factors that may contribute to its occurrence in this population.